2021
DOI: 10.3390/microorganisms9040815
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gut Microbiome Manipulation in 5xFAD Mice on Alzheimer’s Disease-Like Pathology

Abstract: The gut brain axis seems to modulate various psychiatric and neurological disorders such as Alzheimer’s disease (AD). Growing evidence has led to the assumption that the gut microbiome might contribute to or even present the nucleus of origin for these diseases. In this regard, modifiers of the microbial composition might provide attractive new therapeutics. Aim of our study was to elucidate the effect of a rigorously changed gut microbiome on pathological hallmarks of AD. 5xFAD model mice were treated by anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 73 publications
2
16
0
Order By: Relevance
“…An increase in certain bacterial phyla was observed upon probiotic administration (i.e., Actinobacteria, Verrucomicrobia, Bacteroidetes ) ( 50 , 56 ). At the family level, an increase in Peptococcaceae, Ruminococcaceae, Prevotellaceae , S24-7, and Lactobacillaceae was found compared to control group animals ( 49 , 52 , 55 58 , 62 ). An increase in Acetatifactor, Millionella, Alloprevotella, Parabacteroides, Bifidobacterium, Lactobacillus and Bacteroidales was observed compared to AD controls at the genus level ( 47 , 51 53 , 61 ).…”
Section: Resultsmentioning
confidence: 91%
“…An increase in certain bacterial phyla was observed upon probiotic administration (i.e., Actinobacteria, Verrucomicrobia, Bacteroidetes ) ( 50 , 56 ). At the family level, an increase in Peptococcaceae, Ruminococcaceae, Prevotellaceae , S24-7, and Lactobacillaceae was found compared to control group animals ( 49 , 52 , 55 58 , 62 ). An increase in Acetatifactor, Millionella, Alloprevotella, Parabacteroides, Bifidobacterium, Lactobacillus and Bacteroidales was observed compared to AD controls at the genus level ( 47 , 51 53 , 61 ).…”
Section: Resultsmentioning
confidence: 91%
“…miRNA-146a's role and significance in viral-induced encephalopathies and prion disease appear to be expanding. Several attractive and all-encompassing recently proposed theories suggest: (i) that there is a contribution of prions and misfolded proteins in human degenerative diseases that include AD and AMD and other miRNA-146a-associated neurological disorders [56,75,108]; and (ii) that there may be a gastrointestinal (GI)-tract-sourced contribution of microbes or microbial neurotoxins to AD and related neurodegenerative disorders that critically involve miRNA-146a-mediated immunological and/or pro-inflammatory signaling components [108][109][110][111]…”
Section: Discussionmentioning
confidence: 99%
“…Early post-natal antibiotics treatment (P14-P21) resulted not only in long-term alterations of gut microbial genera but also in reduction of brain Aβ deposits and neuroinflammation in aged APPSWE/PS1∆E9 mice. Several publications revealed that antibiotics such as vancomycin, bacitracin, and metronidazole might affect metabolic homeostasis-especially brain insulin sensitivity-in different mouse strains [56][57][58][59]. This might be highly relevant for the observed effects in AD mouse models as a diabetic phenotype contributes to pathogenesis and C57Bl6 mice, often used as disease models, are prodiabetic-in particular, males are prone to obesity.…”
Section: Discussionmentioning
confidence: 99%